2015
DOI: 10.1044/2015_lshss-14-0052
|View full text |Cite
|
Sign up to set email alerts
|

Sample Length Affects the Reliability of Language Sample Measures in 3-Year-Olds: Evidence From Parent-Elicited Conversational Samples

Abstract: Purpose: The goal of this study was to investigate the extent to which sample length affected the reliability of total number of words (TNW), number of different words (NDW), and mean length of C-units in morphemes (MLCUm) in parent-elicited conversational samples for 3-year-olds. Method: Participants were sixty 3-year-olds. A 22-min language sample was collected from each child during free play with the parent in the laboratory. Samples of 1, 3, 7, and 10 min were extracted from the 22-min samples. TNW, NDW, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…(2009) suggested that natural language samples “will typically be at least 30 minutes in length” (p. 645), whereas APPL guidelines suggest a minimum duration of at least 20 min (>30 if possible), with at least 50 spontaneous utterances if feasible based on the child’s developmental level. This is consistent with research showing that relatively short natural language samples can provide reliable information about key language skills (see Guo & Eisenberg, 2015) and increases efficiency of natural language sample collection and transcription when a clinician considers samples shorter than 30 min to be appropriate. Finally, the APPL includes more detailed guidelines regarding calculation of mean length of utterance than are provided by Tager-Flusberg et al.…”
Section: Development Of the Assessment Of Phase Of Preschool Languagesupporting
confidence: 89%
“…(2009) suggested that natural language samples “will typically be at least 30 minutes in length” (p. 645), whereas APPL guidelines suggest a minimum duration of at least 20 min (>30 if possible), with at least 50 spontaneous utterances if feasible based on the child’s developmental level. This is consistent with research showing that relatively short natural language samples can provide reliable information about key language skills (see Guo & Eisenberg, 2015) and increases efficiency of natural language sample collection and transcription when a clinician considers samples shorter than 30 min to be appropriate. Finally, the APPL includes more detailed guidelines regarding calculation of mean length of utterance than are provided by Tager-Flusberg et al.…”
Section: Development Of the Assessment Of Phase Of Preschool Languagesupporting
confidence: 89%
“…However, applying the 100-utterance criterion to the current study would have excluded over 70% of the participant sample at each time point, producing results that were generalizable only to the subgroup of children with ASD with relatively good language and communication skills. A recent study of typically developing children found good internal consistency for MLU across language samples lasting only 1, 3, and 7 min (Heilmann, Nockerts, & Miller, 2010), and a study of 3-year-old children with a range of language abilities found acceptable reliability for NDW and a measure of grammatical complexity for samples between 7 and 10 min (Guo & Eisenberg, 2015). In addition, recent research assessing spoken language in young children with ASD derived MLU from approximately 30 utterances (Kover, Davidson, Sindberg, & Ellis Weismer, 2014).…”
Section: Parent-child Language Samplesmentioning
confidence: 99%
“…Parents were also asked whether their child had received a diagnosis of a neurodevelopmental disorder, such as autism spectrum disorder or cerebral palsy, and whether their child understood or spoke more than one language. The play protocol, drawn from previous studies of conversational language ability, involved presenting the child with a standard set of toys (foam blocks and a farm set) and two popular children's books (DeThorne, Deater-Deckard, Mahurin-Smith, Coletto, & Petrill, 2011;Guo & Eisenberg, 2015;Rice, Redmond, & Hoffman, 2006). Clinicians were instructed to follow the child's lead in play and conversation; engage in parallel talk and "glossing" (repeating back the child's utterances to facilitate transcription); and minimize the use of corrections, yes/no, and wh-questions (DeThorne et al, 2011; Guo & Eisenberg, 2015;Rice et al, 2006).…”
Section: Three-year Data Collectionmentioning
confidence: 99%
“…Approximately 20 min of play were recorded to allow the participants 10 min to "warm up." Conversational language was analyzed in the second 10-min segment-a sample length that has been found to be effective in assessing the language of 3-year-old children (Guo & Eisenberg, 2015). For samples of 20 min or more, the second 10 min of the sample was transcribed.…”
Section: Three-year Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation